Amphipyra livida - Rybalkin, Sergey A. (Zenodo, 2020)
Amphipyra livida (Denis & Schiffermuller, 1775) Fig. 1: 8 Material. Russia: Kunashir Island, 4.5 km NW Mendeleyevo Airport, Tretyakovo village, 2.09– 19.09.2019, 19 ex., leg. S. Rybalkin. Distribution. Russia (Khabarovsky Krai, Sakhalin, Primorsky Krai, Amur Region, S. Siberia, W. Siberia, Ural, European Russia, N. Caucasus), Japan (Hokkaido, Honshu, Shikoku, Kyushu), China, Korea, N. India, Middle Asia, Near East, Transcaucasia, Baltic countries, Belarus, Ukraine, Europe (Lelej 2016). The species is recorded for the first time from the Kuril Islands. Published as part of Rybalkin, Sergey A., 2020, On the knowledge of Lepidoptera of Kunashir Island, Russia, pp. 98-105 in Amurian Zoological Journal XII (2) on page 99, DOI:10.33910/2686-9519-2020-12-2-98-105, http://zenodo.org/record/11362013